Legal Analysis of the Notary's Role in Protecting Client Personal Data - Hayati, Principia Prima Shafa; Nur Rahmat; Jaenudin Umar; Solichin, Solichin (Eastasouth Institute, 2024)
Notaries, empowered to create authentic deeds, require client personal data to perform their duties, making this information vulnerable to misuse if not properly secured. This paper examines the obligations of notaries in protecting client data under the Personal Data Protection Act No. 27 of 2022. Using doctrinal legal research methods, it explores data protection principles, the legal framework for client rights, and how these responsibilities align with notarial duties. Findings reveal that privacy is central to data protection, with the 2022 Act providing a legal foundation for notaries to safeguard client information, emphasizing the importance of maintaining confidentiality in all deed-related activities. The Personal Data Protection Act supports notaries’ roles as data controllers and processors, linking these duties with the authority granted under the Notary Position Act. The synergy between these laws ensures that clients' data rights are upheld, and notarial responsibilities are reinforced within the legal framework.